The Influence of Islamic YouTube Content on Millennial Understanding of Islam - Sajidin, Zayin Nafsaka; Rizki, Muhammad (Islamic Journal of Communication and Public Discourse, 2025)
The development of digital media, particularly YouTube, has changed the landscape of Islamic proselytization among millennials. This platform has become the primary source for young people to understand religious teachings, replacing the dominance of traditional religious institutions. This study aims to evaluate the influence of Islamic content consumption on YouTube on the Islamic understanding of millennials in Indonesia, as well as identify the type of content that most effectively shapes religious perceptions. Using a quantitative correlational approach with a survey method involving 400 respondents, the data were analyzed using Pearson correlation and multiple regression techniques, aided by SPSS 26. The results showed that consuming moderate da'wah content and engaging in intellectual discussions significantly increased the level of rational, inclusive, and critical understanding of Islam, whereas consuming conservative content tended to be negatively correlated with religious openness. Factors such as educational background and religious intensity are also shown to moderate the relationship. The implications of this study emphasize the importance of strengthening religious digital literacy among millennials, developing moderate digital da'wah platforms, and collaboration between content creators, religious institutions, and social media platforms to build a credible and educational digital da'wah ecosystem.